Faktor-Faktor Penyebab Rendahnya Penggunaan Hak Kekayaan Intelektual di Kalangan Usaha Kecil Menengah Batik - V. Selvie Sinaga (Jurnal Hukum IUS QUIA IUSTUM, 2014)
Ideally, the Intellectual Property Rights should not only beof the property of major industries but should also be of the small-medium industries’ property. In fact, there are only few of the small-medium scale industries in Indonesia which utilize the intellectual property rights in their business activities. The problems which would be studied in this research is the factors serving as the challenges for the smallmedium batik industries in Pekalongan and Yogyakarta in using intellectual property rights in their businesses. The method used in this research was empirical approach in form of primary data obtained from the interviews with the representatives of related government institutions and the employers of 14 small-medium scale batik enterprises in Pekalongan and Yogyakarta. This study concludes that in addition to the fact that not all intellectual property rights branches are relevant to batik industries, the batik industry employers both in Pekalongan and Yogyakarta are reluctant to use intellectual property rights due to the complicated, time-consuming, and expensive registration process and the weak law reinforcement related to intellectual property rights violations in Indonesia.